Numerical simulation of thermal conductivity of graphene filled polymer composites. (1st December 2016) - Zhang, Ya-Fei; Zhao, Yun-Hong; Bai, Shu-Lin; Yuan, Xiaowen
Abstract: In this work, the thermal behavior of graphene foam (GF) filled polymer composite is investigated using the finite element method. Owing to the interconnected structure of GF, which forms effective heat pathways, GF filled polymer composite is endowed with good thermal properties. The effect of contact thermal resistance, interfacial thermal conductance, as well as GF strut length and diameter on thermal conductivity is simulated and compared with experimental results. It is found that the contact thermal resistance is more important than interfacial thermal conductance in terms of thermal conductivity of composite. The contact thermal resistance between GF filled polymer composite and copper block is about 10 −4 to 10 −3 m 2 KW −1 . The shorter length and larger radius of GF struts are beneficial for heat dissipation. The results prove that the GF filled polymer composite is a good candidate material for heat management of electronic devices.